Low-Complexity WSRMax Precoder Design Using the Dual Coordinate Ascent Method - Hu, Xianzhi; Dai, Xuchu (IEEE wireless communications letters, 2023)
We propose a low-complexity precoder design for weighted sum rate maximization (WSRMax) in multiuser multiple-input-multiple-output systems with per-antenna power constraints (PAPCs). The proposed design is based on the alternating optimization framework and a fast dual coordinate ascent method in the inner loop. Specifically, the original nonconvex WSRMax problem is first approximated as a sequence of convex quadratic optimization problems subject to PAPCs by adopting alternating optimization. Then, each convex quadratic problem is solved by a dual coordinate ascent method. The proposed dual coordinate ascent method includes no turning parameters, such as the step size in the projected gradient method, which offers both stability and fast convergence. Simulation results show that the dual coordinate ascent method converges faster than existing methods, which significantly improves the total computational efficiency of alternating optimization.